Symmetry breaking above room temperature in an Fe(ii) spin crossover complex with an N4O2 donor set. Issue 8 (11th January 2017) - Phonsri, Wasinee; Davies, Casey G.; Jameson, Guy N. L.; Moubaraki, Boujemaa; Ward, Jas S.; Kruger, Paul E.; Chastanet, Guillaume; Murray, Keith S.
Abstract : An halogen-substituted salicylaldimine iron(ii ) complex shows an abrupt two-step spin transition above room temperature, variable temperature crystallography showing symmetry breaking. Abstract : [Fe(qsal-Cl)2 ] is one of the few known Fe(ii ) spin crossover compounds with an N4 O2 donor atom environment. It shows an abrupt two-step spin transition at 308 and 316 K and importantly, symmetry breaking at the highest temperature reported, to date, in spin crossover compounds.